The Effect Of Compensation On Employee Performance With Work Motivation As An Intervening Variable At The Office Of Cooperative Micro Enterprises, Industry And Trade, Banjar Regency, South Kalimantan - Abdul Kadir (Jurnal Ekonomi, 2024)
This research aims to determine the effect of compensation on employee performance through work motivation in the cooperative and micro-enterprise department of Banjar Regency, South Kalimantan. This type of research uses descriptive quantitative with a survey approach where questionnaires will be distributed to all research respondents, where the population in this research is all employees of the cooperative and micro-enterprise department of Banjar district, South Kalimantan, totaling 35 people. In determining the sample, saturated sampling was used where the entire population was used as respondents considering that the population was less than 100. In testing the results of respondent data to measure the influence of the dependent variable on the independent variable, path analysis was used. The test results showed that compensation was directly proven to have a significant effect on the performance of employees of the cooperative and micro-enterprise department of Banjar district, South Kalimantan, indirectly, motivation was able to mediate the effect of compensation on the performance of employees of the cooperative and micro-enterprise department of Banjar district, South Kalimantan.